Pengaruh Kesadaran Wajib Pajak, Kualitas Pelayanan Fiskus, Sanksi Perpajakan, Lingkungan Wajib Pajak Berada Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus Wajib Pajak Orang Pribadi di KPP Pratama Bangkalan) - Zahro, Aminatus; Mawardi, M. Cholid; Sari, Arista Fauzi Kartika (Universitas Islam Malang, 2023)
This study aims to determine the effect of taxpayer awareness, the quality of taxpayer services, tax sanctions and the taxpayer's environment on taxpayer compliance. researchers set active and registered individual taxpayers at the North Malang Primary Tax Service Office as the population. While the researchers used the Slovin formula in determining the sample with a total of 100 taxpayer respondents. The research method used is quantitative research of primary data with questionnaire data collection techniques using a 5-point Likert scale. The data analysis method used is multiple linear regression analysis using IBM SPSS tools. The results of this study indicate the results that taxpayer awareness, the quality of taxpayer services, tax sanctions and the taxpayer environment have a simultaneous effect on taxpayer compliance. While partially taxpayer awareness has a positive effect on taxpayer compliance, the quality of taxpayer services has no effect on taxpayer compliance, tax sanctions have a positive effect on taxpayer compliance, and the taxpayer environment has no effect on taxpayer compliance.Keywords: Taxpayer awareness, taxpayer service quality, tax sanctions, taxpayer environment, taxpayer compliance.